School District Reorganization in Maine: Lessons Learned for Policy and Process - Fairman, Janet; Donis-Keller, Christine (Maine Policy Review, 2012)
In 2007, Maine’s legislature enacted a law mandating school district consolidation with the goal of reducing the state’s 290 districts to approximately 80. Five years later the success of this policy is open to debate. Janet Fairman and Christine Donis-Keller examine what worked and what didn’t work in this effort to consolidate school districts and provide a list of “lessons learned,” with clear implications for the design and implementation of state educational policy.